A torsional MRE joint for a C-shaped robotic leg. (18th November 2016) - Christie, M D; Sun, S S; Ning, D H; Du, H; Zhang, S W; Li, W H
Abstract: Serving to improve stability and energy efficiency during locomotion, in nature, animals modulate their leg stiffness to adapt to their terrain. Now incorporated into many locomotive robot designs, such compliance control can enable disturbance rejection and improved transition between changing ground conditions. This paper presents a novel design of a variable stiffness leg utilizing a magnetorheological elastomer joint in a literal rolling spring loaded inverted pendulum (R-SLIP) morphology. Through the semi-active control of this hybrid permanent-magnet and coil design, variable stiffness is realized, offering a design which is capable of both softening and stiffening in an adaptive sort of way, with a maximum stiffness change of 48.0%. Experimental characterization first serves to assess the stiffness variation capacity of the torsional joint, and through later comparison with force testing of the leg, the linear stiffness is characterized with the R-SLIP-like behavior of the leg being demonstrated. Through the force relationships applied, a generalized relationship for determining linear stiffness based on joint rotation angle is also proposed, further aiding experimental validation.